Initiation of insulin therapy in patients with type 2 diabetes: An observational study - Zerovnik Spela; Kos Mitja; Locatelli Igor (Acta Pharmaceutica)
The aim of the study was to assess the initiation of insulin therapy in patients with type 2 diabetes using health claims data on prescription medicines. The study evaluated time to insulin initiation and prescribing patterns of other anti-diabetic medicines before and after insulin initiation. Five years after starting non-insulin antidiabetic therapy, 6.4 % of patients were prescribed insulin, which is substantially lower compared to other similar studies. Among all patients who initiated insulin therapy in 2013, 30 % did not continue any other antidiabetic therapy. However, this proportion was lowered to 20 % in 2018. Before insulin initiation in 2018, metformin was prescribed in only 67 % of patients and sulfonylureas in 78 % of patients. Moreover, metformin and sulfonylureas were discontinued after insulin initiation in 26 and 37 % of patients, resp. More attention should be paid to the continuation of oral anti-diabetics, particularly metformin, after insulin initiation.